Impact of synthetic insecticides on the life table parameters of Trichogramma chilonis under laboratory conditions - Muhammad Salim; Arsalan Arif; Muhammad Ayaz; Ahmad Ur Rahman Saljoqi; Ayhan Gökçe; Haroon Khan; Shahid Sattar; Bashir Ahmad; Shah Alam Khan (Scientific Reports)
Abstract Trichogramma chilonis (Ishii) is an important egg parasitoid of Helicoverpa species in tomato growing areas of Pakistan. Different insecticides are used for the management of H. armigera, but these insecticides have significantly reduced the effectiveness of T. chilonis. Therefore, this research aims to understand the compatibility of the selected insecticides with biological control strategies involving T. chilonis for managing Helicoverpa armigera in tomato-growing areas. For this purpose, the effects of five insecticides namely Novaluron, Bifenthrin, Emamectin Benzoate, Chlorantraniliprole and Imidacloprid were assessed against T. chilonis under laboratory conditions. The assays involved direct applications of different insecticides on Sitotroga cerealella eggs and their subsequent effect of T. chilonis life history parameters. A total of 200 eggs were used in each treatment. The results revealed that all the tested insecticides had subsequent negative effects on T. chilonis performance. The results showed that the insecticides Imidacloprid and Chlorantraniliprole led to low mean fecundity, minimum number of male and female adults emergence and prolonged the total pre-oviposition period of T. chilonis as compared to Bifenthrin and Novaluron. The bootstrap results recorded the highest value of the net reproductive rate (R 0), intrinsic rate of increase (r) and the finite rate of increase (λ) of T. chilonis in host eggs treated with Bifenthrin and Novaluron as compared to the other tested chemicals. The results regarding percent parasitism showed that maximum percent parasitism was noted in control, Bifenthrin and Novaluron, while the insecticides Imidacloprid and Chlorantraniliprole resulted in minimum % parasitism (63.5% and 71%) respectively. The study revealed that Bifenthrin and Novaluron are relatively more compatible with the T. chilonis in the different integrated pest management programs for H. armigera as compared to other tested chemicals.